2021
DOI: 10.1093/mnras/stab096
|View full text |Cite
|
Sign up to set email alerts
|

The IRX–β relation of high-redshift galaxies

Abstract: The relation between infrared excess (IRX) and UV spectral slope (βUV) is an empirical probe of dust properties of galaxies. The shape, scatter, and redshift evolution of this relation are not well understood, however, leading to uncertainties in estimating the dust content and star formation rates (SFRs) of galaxies at high redshift. In this study, we explore the nature and properties of the IRX-βUV relation with a sample of z = 2 − 6 galaxies (M* ≈ 109 − 1012 M⊙) extracted from high-resolution cosmological s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 225 publications
(367 reference statements)
8
25
0
Order By: Relevance
“…Thus, intrinsic red stellar colours could explain the data points lying below the SMC and Calzetti lines in the IRX-β diagram. This result is consistent with previous theoretical studies such as Popping et al (2017), Narayanan et al (2018a) and Liang et al (2021). Burgarella et al (2020), based on their SED fitting analysis, showed that older LBGs tend to occupy the lower part of the IRX-β diagram.…”
Section: Possible Other Effectssupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, intrinsic red stellar colours could explain the data points lying below the SMC and Calzetti lines in the IRX-β diagram. This result is consistent with previous theoretical studies such as Popping et al (2017), Narayanan et al (2018a) and Liang et al (2021). Burgarella et al (2020), based on their SED fitting analysis, showed that older LBGs tend to occupy the lower part of the IRX-β diagram.…”
Section: Possible Other Effectssupporting
confidence: 93%
“…These data are just used as guides or references for our results, and are not intended for detailed comparison or fitting. We also note that the observational data have large uncertainties; for example, IRX depends on the assumption for the dust temperature (50 K is adopted for the data from Hashimoto et al 2019), whose 1σ uncertainty is typically 10 K. The value of β depends on the choice of the observing wavelengths (Popping et al 2017;Liang et al 2021). Many of the LBGs at z 6 are not detected, even by ALMA (e.g.…”
Section: Irx-β Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujimoto et al 2017;Hashimoto et al 2019;Novak et al 2020). We examine 𝑅 = 5 kpc for a case of moderate extinction, and shrink This can be directly interpreted as an observed (or luminosity-weighted) dust temperature ('effective dust temperature' in Liang et al 2019). The temperature range is roughly consistent with that assumed in the above mentioned observational studies.…”
Section: Well-mixed Geometrysupporting
confidence: 56%
“…The value of the discrepancy depends on the correction factor employed from Suess et al (2019b). We emphasize that Figures 2 and B1 should be understood as illustrations rather than proper com-parisons with observations; we plan to analyse synthetic images of FIREbox galaxies using radiative transfer (e.g., Liang et al 2019Liang et al , 2021 in future work. Shibuya et al (2015) find that a log-normal distribution well approximates the 𝑅 eff distribution in their combined legacy dataset of 3D-HST, CANDELS, Hubble Ultra Deep Fields (HUDF) 09+12 and the Hubble Frontier Fields (HFF) surveys.…”
Section: Comparisons To Observationsmentioning
confidence: 99%